Evaluation of Antimicrobial Efficacy of 5% Myristica Fragrans Mouthwash in Gingivitis Subjects - A Clinico Microbiological Study (International Journal of Ayurveda and Pharma Research, 2024)
Gingivitis is the inflammation or infection of gingiva that support the teeth. The prevailing belief regarding the cause for gingivitis is the toxins produced by the bacteria in the mouth, particularly the bacteria that causes the formation of plaque. Myristica fragrans commonly known as nutmeg possesses anti-carcinogenic, anti-inflammatory activities, antioxidant effect, anti-diabetic, and antibacterial properties. The seeds of nutmeg have the ability to inhibit the growth of Gram Negative and Positive bacteria. Objective: 1. To evaluate clinical parameters at baseline and 21 days post scaling after the use of Myristica fragrans mouthwash. 2. To evaluate the colony count of Porphyromonas gingivalis in plaque samples at baseline and 21 days after the use of Myristica fragrans mouthwash. Methodology: A total of 40 gingivitis subjects were selected and divided randomly into Group A and B. Group A, Non-surgical periodontal therapy followed by Myristica fragrans mouthwash (20) and Group B, Non-surgical periodontal therapy alone (20). The supragingival plaque samples were collected at baseline and 21 days after non surgical periodontal therapy. Results: Significant reduction in clinical parameters and colony count of Porphyromonas gingivalis after the use of 5% Myristica fragrans mouthwash.